Effects of footedness and stance asymmetry confirm an inter-leg metastable coordination dynamics of standing posture. Issue 2 (4th March 2021) - Harrison, Steven J.; Kinsella-Shaw, Jeffrey M.; Dotov, Dobromir
Abstract: We investigated the patterns of coordination between the left and right legs that support the task of maintaining an upright standing posture. We used cross-wavelet analyses to assess coordination between the centers of pressure under the left and right feet. We recruited participants with a lateralized functional preference for their right leg, and we manipulated whether these participants stood with symmetric/asymmetric stances and whether their eyes were open or closed. Our hypotheses were derived from the Haken-Kelso-Bunz (HKB) model of interlimb coordination dynamics. Consistent with HKB model predictions, we observed (1) coordination taking the form of metastable, transient epochs of stable phase relations, (2) preferences for in-phase and anti-phase coordination patterns, and (3) changes in pattern stability and phase leads associated with both stance asymmetry and right-side lateral preference. The form and stability of observed coordination patterns were mediated by the availability of visual information. Our findings confirm the existence of a metastable coordination dynamic associated with the task of maintaining upright stance. We discuss the implications of these findings in the context of evaluating the utility of the HKB model for understanding the functional organization of the posture system.